The influence of excess K2O on the electrical properties of (K,Na)1/2Bi1/2TiO3 ceramics - Li, Linhao; Li, Ming; Sinclair, Derek C. (American Institute of Physics, 2018)
The solid solution (KxNa0.50-x)Bi0.50TiO3 (KNBT) between Na1/2Bi1/2TiO3 (NBT) and K1/2Bi1/2TiO3 (KBT) has been extensively researched as a candidate lead-free piezoelectric material because of its relatively high Curie temperature and good piezoelectric properties, especially near the morphotropic phase boundary (MPB) at x ~ 0.10 (20 mol% KBT). Here we show low levels of excess K2O in the starting compositions, i.e. (Ky+0.03Na0.50-y)Bi0.50TiO3.015 (y-series), can significantly change the conduction mechanism and electrical properties compared to a nominally stoichiometric KNBT series (KxNa0.50-x)Bi0.50TiO3 (x-series). Impedance Spectroscopy measurements reveal significantly higher bulk conductivity (σb) values for y ≥ 0.10 samples (activation energy, Ea, ≤ 0.95 eV) compared to the corresponding x-series samples which possess band-gap type electronic conduction (Ea ~ 1.26 to 1.85 eV). The largest difference in electrical properties occurs close to the MPB composition (20 mol% KBT) where y = 0.10 ceramics possess b (at 300 oC) that is 4 orders of magnitude higher than x = 0.10 and the oxide-ion transport number in the former is ~ 0.70 – 0.75 compared to < 0.05 in the latter (between 600 and 800 oC). The effect of excess K2O can be rationalised on the basis of the (K + Na):Bi ratio in the starting composition prior to ceramic processing. This demonstrates the electrical properties of KNBT to be sensitive to low levels of A-site nonstoichiometry and indicates excess K2O in KNBT starting compositions to compensate for volatilisation can lead to undesirable high dielectric loss and leakage currents at elevated temperatures.